STRENGTHENING RISK MANAGEMENT OF SHARIA BANKING IN INDONESIA - Miftah Idris (FAKULTAS HUKUM UM PAREPARE, 2019)
The risk faced by sharia banking in channeling funds through financing is the biggest source of risk for business operations, because the presence of problematic financing not only lowers income for Islamic banks but also affects the health of Islamic banks. Therefore, risk management is needed to identify, measure, monitor and control risks in accordance with Islamic banking business activities. The purpose of this study is how efforts are made to improve the optimization of risk management in Islamic Banking. The research method used is descriptive legal research or literature with a type of qualitative research. The results of the study found that there is a need for optimization of institutions and systems in strengthening risk management in Islamic banking today